Autophagy induction by SIRT6 is involved in oxidative stress-induced neuronal damage - Jiaxiang Shao; Xiao Yang; Tengyuan Liu; Tingting Zhang; Qian Reuben Xie; Weiliang Xia (Protein & Cell, 2016)
Abstract SIRT6 is a NAD+-dependent histone deacetylase and has been implicated in the regulation of genomic stability, DNA repair, metabolic homeostasis and several diseases. The effect of SIRT6 in cerebral ischemia and oxygen/glucose deprivation (OGD) has been reported, however the role of SIRT6 in oxidative stress damage remains unclear. Here we used SH-SY5Y neuronal cells and found that overexpression of SIRT6 led to decreased cell viability and increased necrotic cell death and reactive oxygen species (ROS) production under oxidative stress. Mechanistic study revealed that SIRT6 induced autophagy via attenuation of AKT signaling and treatment with autophagy inhibitor 3-MA or knockdown of autophagy-related protein Atg5 rescued H2O2-induced neuronal injury. Conversely, SIRT6 inhibition suppressed autophagy and reduced oxidative stress-induced neuronal damage. These results suggest that SIRT6 might be a potential therapeutic target for neuroprotection.